Total Synthesis of Anti‐MRSA Active Diorcinols and Analogues. Issue 44 (1st July 2020) - Boehlich, G. Jacob; de Vries, Jessica; Geismar, Olivia; Gudzuhn, Mirja; Streit, Wolfgang R.; Wicha, Sebastian G.; Schützenmeister, Nina
Abstract: Diorcinols and related prenylated diaryl ethers were reported to exhibit activity against methicillin‐resistant clinical isolates of Staphylococcus aureus (MRSA). Within these lines, we report the first total synthesis of diorcinol D, I, J, the proposed structure of verticilatin and recently isolated antibacterial diaryl ether by using an efficient and highly divergent synthetic strategy. These total syntheses furnish the diaryl ethers in only five to seven steps employing a Pd‐catalyzed diaryl ether coupling as the key step. The total synthesis led to the structural revision of the natural product verticilatin, which has been isolated from a plant pathogenic fungus. Furthermore, these structures were tested in order to determine their antibacterial activities against different MRSA strains as well as further Gram‐positive and ‐negative bacteria. Abstract : Family reunion—the 7 kids of Dimethylorcinol ! A short and divergent total synthetic approach towards diorcinols and related structures yielded seven different diaryl ethers. A Pd‐catalyzed diaryl ether coupling was identified as the key step. Three members of the natural product class family exhibit anti‐MRSA and biofilm activity (see scheme).